Software-Defined Networking: Revolutionizing Network Management and Optimization - Sabda Maulana; Sheila Aulia Anjani; Yulia Putri Ayu Sanjaya; Sondang Visiana S; Precious Sithole (Pandawan Sejahtera Indonesia, 2024)
This study investigates the impact of Software-Defined Networking (SDN) on network management and optimization, comparing its performance to traditional networking approaches. Through a mixed-methods approach, including empirical experiments and expert interviews, the research demonstrates that SDN significantly enhances network performance by reducing latency, increasing throughput, and providing superior security management. The scalability of SDN was also confirmed, with the network efficiently handling an increasing number of devices without performance degradation. However, the study identified challenges in integrating SDN into existing infrastructures and the need for specialized skills to manage SDN environments effectively. These findings underscore the potential of SDN as a transformative technology in modern network management, while also highlighting areas where further research is needed to address integration and skill-related challenges.